Recurrent Verruca Vulgaris Treated with Combination of 80% Trichloroacetate and Electrosurgery: a Case Report - Nyoman Yoga Maya Pramita; Ketut Kwartantaya Winaya; I Gusti Nyoman Darmaputra (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Verruca vulgaris is one of the most common benign skin tumor caused by human papillomavirus (HPV) type  1, 2, 3, 4, 27 and 57. HPV caused infection is often recurrent leading to frustration due to loss of time and medical expenses. Monotherapy gives a varied response, and in the case of recurrence, combination therapy can be an option. Purpose: To evaluate the cause and management of recurrent verruca vulgaris. Case: This is a case report of a 33 years-old man complaining of a recurrent wart with a rough surface on his right index finger in the past three months. Initially the patient was treated with electrosurgery, but the warts came back. The patient was a smoker. The warts disappeared after electrosurgery and two sessions of 80% trichloroacetate (TCA), and at the 4th week of observation no new lesion was reported. Discussion: Recurrence of verruca vulgaris often occurs using monotherapy, thus requires other modalities. The combination of electrocautery and 80% TCA provides good clearance with low recurrence. Conclusion: Combination treatment for recurrent warts is effective for clearing the lesion and prevent recurrence.